Developing Augmented Reality-Based Modules for Strengthening Pancasila Student Profiles in Elementary School Students - Sukirno, Sukirno; Marjanah, Marjanah; Isda, Irma Dewi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This research aims to develop an Augmented Reality media-based module with learning the Pancasila Student Profile Strengthening Project that is feasible and effective for fourth-grade students in elementary schools. This research starts by examining the demands and traits of the prospective audience, then continues with the design of a module that utilizes AR technology to provide a more dynamic learning experience. This study employed the research and development method with the ADDIE model, which consists of five main stages: analysis, design, development, implementation, and evaluation. The data analysis techniques employed included qualitative and quantitative descriptive approaches. Qualitative data were obtained from observations of the implementation of the teaching module, while quantitative data were obtained from assessments by content experts and material experts, as well as from questionnaires. The results indicated that the media expert validation reached a percentage of 90.97%, and material experts reached 85.00%, both of which fall into the ’excellent’ category. Therefore, the media was deemed suitable for use in learning. The field trial involved 60 students. The results showed that in the small group trial, the media obtained a percentage value of 90.63%, categorized as ’excellent’, while in the large group trial, it obtained a percentage value of 92.73%, also categorized as ’excellent’. Based on the feasibility and effectiveness evaluations, the module is suitable and effective for use by fourth-grade students of SD Negeri Tualang Cut Aceh Tamiang. Thus, the AR-based module is an innovation that can enhance the quality of learning by making content dynamic and interactive.